2014
DOI: 10.9755/ejfa.v26i3.16437
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transformation efficiency of five Agrobacterium tumefaciens strains in Nicotiana Tabacum L.

Abstract: Agrobacterium mediated transformation has been widely used for research in plant molecular biology and for genetic improvement of crops exploiting its tremendous ability to transfer foreign DNA to plants. In this study, the transformation efficiency of five Agrobacterium tumefaciens strains GV2260, LBA4404, AGL1, EHA105, and C58C1 was evaluated in Nicotiana tabacum L. cultivar Samsun. The Agrobacterium strains contained the recombinant binary vector pBin19 harboring beta-glucuronidase uidA gene under 35S promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 18 publications
2
21
1
3
Order By: Relevance
“…Thus, the transformation efficiency of MNH-786 and VH-289 was 3.75 % and 2.88 %, respectively (Table 3). Bakhsh et al [48] reported higher transformation efficiency (20 %) of Agrobacterium strain (LBA4404) in tobacco plants [48], but cotton is harder to transform, and our results were similar to the work of Majeed et al [49] in which transformation efficiency in cotton was 5.17 % [49, 50]. …”
Section: Discussionsupporting
confidence: 89%
“…Thus, the transformation efficiency of MNH-786 and VH-289 was 3.75 % and 2.88 %, respectively (Table 3). Bakhsh et al [48] reported higher transformation efficiency (20 %) of Agrobacterium strain (LBA4404) in tobacco plants [48], but cotton is harder to transform, and our results were similar to the work of Majeed et al [49] in which transformation efficiency in cotton was 5.17 % [49, 50]. …”
Section: Discussionsupporting
confidence: 89%
“…The Agrobacterium-mediated binary vector system is an efficient system of natural exchange of genetic material. Based on our earlier experiments, we used the LBA4404 agrobacterium strain harboring pRD400 plasmid to infect apical meristems in genetic transformation experiments [39]. The transformation efficiency achieved in the present study has been low compared to earlier studies [40][41][42]25].…”
Section: Discussionmentioning
confidence: 89%
“…The suitability of C58C1 strain harbouring various plasmids for the transformation of many economic plants has already been reported (Bakhsh et al 2014). This study used shoot tip explants taken from in vitro grown stock material multiplied on MS medium containing 1.0 mg/l BA for 6 weeks following Karataş and Aasim (2015).…”
Section: Resultsmentioning
confidence: 99%
“…43 out of 78 plants (55.13%) plants showing regeneration on MS medium supplemented with Kanamycin were speculated a escapes that were further confirmed by GUS histochemical analysis. Although Kanamycin is believed to be a good selection agent for putative plants, still escapes have been documented in various genetic transformation studies (Bakhsh et al, 2014;McCormick et al, 1986).…”
Section: Resultsmentioning
confidence: 99%